If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + 6) + ln(x + -6) = ln(7) Reorder the terms: ln(6 + x) + ln(x + -6) = ln(7) (6 * ln + x * ln) + ln(x + -6) = ln(7) (6ln + lnx) + ln(x + -6) = ln(7) Reorder the terms: 6ln + lnx + ln(-6 + x) = ln(7) 6ln + lnx + (-6 * ln + x * ln) = ln(7) 6ln + lnx + (-6ln + lnx) = ln(7) Reorder the terms: 6ln + -6ln + lnx + lnx = ln(7) Combine like terms: 6ln + -6ln = 0 0 + lnx + lnx = ln(7) lnx + lnx = ln(7) Combine like terms: lnx + lnx = 2lnx 2lnx = ln(7) Reorder the terms for easier multiplication: 2lnx = 7ln Solving 2lnx = 7ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-7ln' to each side of the equation. -7ln + 2lnx = 7ln + -7ln Combine like terms: 7ln + -7ln = 0 -7ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-7 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-7 + 2x)' equal to zero and attempt to solve: Simplifying -7 + 2x = 0 Solving -7 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 0 + 7 2x = 0 + 7 Combine like terms: 0 + 7 = 7 2x = 7 Add '-2x' to each side of the equation. 2x + -2x = 7 + -2x Combine like terms: 2x + -2x = 0 0 = 7 + -2x Simplifying 0 = 7 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 26-3y-3y=4 | | 6x^2+19-8=0 | | 1.5x+25y=600 | | 3x^2+2x+4=12 | | 2x+9=-11-2x | | 3x+45.87= | | 2+3x=-8+x | | lnx+ln(x+7)=1 | | 2z+12=36 | | 10x-y=53 | | 14x+2y=8 | | 2x^3+21x+17x^2=0 | | 5x+3y^2=12 | | 56a+43=32a | | e+r=s | | 3x^2+6x+4=12 | | r=ht | | 81k^2+-1=8 | | 9(9-8x-4x)+8(3x+4)=11 | | r+m=b | | x^3-61=3 | | -4x^2+8x+11=0 | | 12t^2=27+27t | | .5x^2+2x-30=0 | | 10w^2-200=0 | | 8x+-2=6x | | 8x-2=6x | | w^2+11w-200=0 | | lnx=-4.833559 | | (8b^4-b^3)-(b^4+4b^3-4)= | | 4x^4+2x^3-108x-54=0 | | y^2+8x+16=0 |